2018
DOI: 10.1051/epjconf/201817009005
|View full text |Cite
|
Sign up to set email alerts
|

A large area diamond-based beam tagging hodoscope for ion therapy monitoring

Abstract: Abstract-. The MoniDiam project is part of the French national collaboration CLaRyS (Contrôle en Ligne del'hAdronthérapie par RaYonnements Secondaires) for on-line monitoring of hadron therapy. It relies on the imaging of nuclear reaction products that is related to the ion range. The goal here is to provide large area beam detectors with a high detection efficiency for carbon or proton beams giving time and position measurement at 100 MHz count rates (beam tagging hodoscope). High radiation hardness and intri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…For the LPSC diamond detectors: sCVD, pCVD, and DOI, labelled respectively A, C, and F in Table 1, an aluminum disk shaped-metallization was locally performed using DMW (Distributed Microwave Plasmas), a technology developed at LPSC [21] and already described in [22]. For the pCVD detectors D and E, the metallization was performed at NANOFAB at Institut Néel using a liftoff process as described in [10].…”
Section: Detector Housingmentioning
confidence: 99%
See 2 more Smart Citations
“…For the LPSC diamond detectors: sCVD, pCVD, and DOI, labelled respectively A, C, and F in Table 1, an aluminum disk shaped-metallization was locally performed using DMW (Distributed Microwave Plasmas), a technology developed at LPSC [21] and already described in [22]. For the pCVD detectors D and E, the metallization was performed at NANOFAB at Institut Néel using a liftoff process as described in [10].…”
Section: Detector Housingmentioning
confidence: 99%
“…For the pCVD detectors D and E, the metallization was performed at NANOFAB at Institut Néel using a liftoff process as described in [10]. The sensor contact for the disk-shaped metallization consists of a 50 nm (LPSC [22]) or a 100 nm (NANOFAB [10]) thick aluminum layer deposited on both sides. A recent study [10] has proven the "blocking", Schottky-like, nature of such aluminum electrodes.…”
Section: Detector Housingmentioning
confidence: 99%
See 1 more Smart Citation
“…Thin ultra-fast silicon detectors (UFSD) have been explored for such purpose [43]. Using another technology, we have shown that a temporal resolution close to 100 ps rms is expected by means of diamond detectors, on condition that large areas are available with detector-grade crystals [24,44]. Relatively large polycrystalline diamonds are available and provide such a time resolution for highly ionizing particles such as carbon ions.…”
Section: Need For a Beam Tagging Systemmentioning
confidence: 99%
“…The 3D diamond sensor permits to reach greater performance in the high‐luminosity areas of the LHC experiments, along with the typical high radiation hardness and extreme resistivity values found in bulk diamond . Commercial CVD diamonds are also studied for their applicability as a sensitive detector in hadron therapy with very promising results as prompt‐gamma and beam tagging hodoscope in ion monitoring …”
Section: Introductionmentioning
confidence: 99%